Correlates of atherosclerotic cardiovascular disease risk in older Colorado firefighters. (17th January 2018) - Li, K; Ochoa, E; Lipsey, T; Nelson, T
Abstract: Background: It has been documented that cardiovascular disease is the leading cause of mortality in on-duty firefighters and little is known about the association between cardiorespiratory fitness and 10-year risk of atherosclerotic cardiovascular disease (ASCVD). Aims: To estimate the probability of 10-year ASCVD risk and its association with per cent body fat (%BF), metabolic syndrome (MetS) and physical fitness in Colorado firefighters. Methods: Ten-year ASCVD risk was calculated using the newly developed pooled cohort equations in firefighters. Logistic regression was conducted to examine the association of 10-year ASCVD risk (<5 versus ≥5%) with estimated maximum volume of oxygen (VO2 max), %BF and MetS. Results: Out of 294 firefighters, 9% had a 10-year ASCVD risk >5%. In the unadjusted models, %BF (odds ratio [OR] = 1.13, P < 0.01), VO2 max (OR = 2.87, P < 0.05) and MetS (OR = 2.66, P < 0.05) were significantly associated with 10-year ASCVD risk. In the adjusted model, only %BF (OR = 1.17, P < 0.01) was significantly associated with 10-year ASCVD risk. Conclusions: Among Colorado firefighters, %BF, but not cardiorespiratory fitness, was independently associated with 10-year ASCVD.